Warming up for mechanosynthesis – temperature development in ball mills during synthesis. Issue 10 (18th January 2017) - Kulla, Hannes; Wilke, Manuel; Fischer, Franziska; Röllig, Mathias; Maierhofer, Christiane; Emmerling, Franziska
Abstract : We present a first direct measurement of the temperature during milling combined with in situ Raman spectroscopy monitoring. Abstract : We present a first direct measurement of the temperature during milling combined with in situ Raman spectroscopy monitoring. The data reveal a low temperature increase due to the mechanical impact and clear temperature increases as a consequence of the reaction heat. Based on the data, temperature rises as postulated in the magma plasma and hot spot theory can be excluded for soft matter milling syntheses.